Analisis Perbandingan Profitabilitas Sebelum Dan Sesudah Akuisisi Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Dewi Meilinda Panduwinata; Isni Andriana; Kemas M.Husni Thamrin (UNIVED Press, 2022)
This study aims to analyze differences in profitability before and after the acquisition. The profitability ratios used in this study are the ratio of GPM, NPM, OPM, ROA, ROE and EPS. The population in this study is a manufacturing company that made acquisitions in 2014. The sample of this study was determined by purposive sampling so that a sample of 4 companies was obtained. The analytical method used in this research is the ANOVA test. The results showed that only the ROE ratio had a difference after the acquisition. While the ratio of GPM, NPM, OPM, ROA and EPS there is no significant difference before and after the acquisition. The results of the study indicate that the economic objective of the acquisition, namely to obtain synergies, was not achieved.